TLC and GC-MS Analyses of Essential Oil Isolated from Macedonian Foeniculi fructus - Menče Najdoska; Jane Bogdanov; Zoran Zdravkovski (University Ss Cyril and Methodius in Skopje, Faculty of Pharmacy and Macedonian Pharmaceutical Association, 2011)
The essential oil of Foeniculi fructus, the ripe fruit from the plant Foeniculum vulgare Mill. ssp. vulgare var. dulce Batt. and Trab. (sweet fennel, македонски анасон) was isolated and the main components were identified and quantified using thin-layer chromatography (TLC) and gas chromatography and mass spectrometry (GC-MS). The Aetherloeum Foeniculi had pale yellow color and characteristic pleasant odor and was obtained in 3.2% yield (by weight from the plant fruits). The main components of the oil were: trans-anethole, 1, (70%), p-anisaldehyde, 2, (19%) estragole, 3, (6%) and anisacetone, 4, (2%). The identity of the components was determined by matching the mass spectra to the library spectra. The identity of the main component, trans-anethole, was confirmed directly by isolation using column chromatography and indirectly by potassium permanganate oxidation of the essential oil. The oxidation product from this reaction, pmethoxybenzoic acid, 16, was isolated and characterized. The potential products of autooxidation of trans-anethole (epoxy anethole, anethole glycol and 16) were not detected in the freshly obtained essential oils.